Decreased Phosphorylation of Y14Caveolin-1 in Endometrial Tissue of Polycystic Ovary Syndrome Patients may be Related with an Insulin Resistant State in this Tissue - Ormazabal, P.; Romero, C.; Gabler, F.; Quest, A.F. G.; Vega, M. (Hormone and Metabolic Research, 2013)
Endometrial tissue of patients with polycystic ovary syndrome (PCOS) shows an impaired expression of insulin signaling molecules. Tyrosine phosphorylation of the insulin receptor (IR) by insulin promotes glucose uptake by activating the PI3K/Akt pathway. IR stability and function depend on the presence of the protein caveolin-1. Activation of IR increases phosphorylation of Y14caveolin-1. Since the endometrium of PCOS patients is proposed to be insulin resistant, we evaluated the phosphorylation of IR and caveolin-1 in endometria of patients with insulin resistance (PCOSE-IR) compared to controls (CE). To explore the mechanism associated with this condition, cultured endometrial cells (T-HESC) were exposed to high glucose (25 mM, 24 h), an experimental condition that leads to insulin resistance in other cell types. Endometrial protein levels of phospho-Y972IR, phospho-Y14caveolin-1 and caveolin-1 were determined by Western blotting. In cultured cells, protein levels of caveolin-1, IR, and Akt were evaluated by Western blotting. After acute insulin stimulation, phospho-S473Akt, phospho-Y14caveolin-1, and 2-deoxyglucose (2-DOG) uptake were determined. PCOSE-IR samples showed high protein levels of caveolin-1, but reduced phospho-Y14caveolin-1 compared to CE. No differences were observed for phospho-Y972IR between both groups. Cells pretreated with glucose showed a reduction in protein levels of IR and caveolin-1 and were unable to increase 2-DOG uptake, phospho-S473Akt and phospho-Y14caveolin-1 after insulin stimulation. In conclusion, in PCOSE-IR the impaired phosphorylation of IR downstream molecules such as phospho-Y14caveolin-1 suggests a diminished insulin sensitivity in endometria, condition that could be supported in vitro by the ability of T-HESCs to become insulin resistant when they are exposed to high glucose.
Keywords: endometrial cells; high glucose; PCOS; caveolin-1